1992
DOI: 10.1144/gsl.sp.1992.066.01.10
|View full text |Cite
|
Sign up to set email alerts
|

The use of ground electrical survey methods for siting water-supply boreholes in shallow crystalline basement terrains

Abstract: Resistivity methods are widely used as an aid to siting water-supply boreholes in basement terrain. Adverse conditions due to shallow bedrock can be identified readily but specific targets such as narrow conductive zones may be missed; quantitative interpretation may be less reliable than is often assumed. Electromagnetic (EM) profiling will detect localized zones of deeper weathering and the effects of fracturing at shallow depths, and it is used for the precise location of anomalous ground indicated by linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…The thickness of the weathered zone is assumed to vary between a minimum of 5.75 m (depth 8.25 m) at the centre of the model structure where the least weathering occurs to a maximum of 13.50 m (depth 16.0 m) at the edges of the model considered to be most weathered. The weathered zone in crystalline basement complex is a product of chemical weathering which is usually a low resistive saprolite overlying a more resistive basement rocks (Carruthers and Smith 1992;Hazell et al 1992). In addition, this zone is commonly aquiferous; thus, low resistivity model values varying between 150 and 100 X m were assigned to this layer.…”
Section: Description Of the Synthetic Modelsmentioning
confidence: 99%
“…The thickness of the weathered zone is assumed to vary between a minimum of 5.75 m (depth 8.25 m) at the centre of the model structure where the least weathering occurs to a maximum of 13.50 m (depth 16.0 m) at the edges of the model considered to be most weathered. The weathered zone in crystalline basement complex is a product of chemical weathering which is usually a low resistive saprolite overlying a more resistive basement rocks (Carruthers and Smith 1992;Hazell et al 1992). In addition, this zone is commonly aquiferous; thus, low resistivity model values varying between 150 and 100 X m were assigned to this layer.…”
Section: Description Of the Synthetic Modelsmentioning
confidence: 99%
“…A common exploration strategy for groundwater in a crystalline basement terrains like this study area is to site water supply borehole where the regolith is thickest, the expectation being that it is under such circumstances that the saturated thickness is greater and the frequency of bedrock fissures also greater (Beeson and Jones, 1988;Carruthers and Smith, 1992;Chilton and Foster, 1995). However, in this aspect of research, there was a consideration on other parameters for deciding on the optimal and reliable borehole site.…”
Section: Criteria For Selecting Good Borehole Sites Within Study Areamentioning
confidence: 99%
“…Resistivity surveys are also commonly used to map fracture zones in hard rock terrain [1] and [2] because high resistivity contrasts usually occur between solid rocks and saturated fracture zones. It has also been revealed that the success of borehole siting in this kind of environment depends on the borehole intersecting some fracture zone in the bedrock.…”
Section: Imentioning
confidence: 99%